Indications for and Technical Aspects of Colorectal Endoscopic Submucosal Dissection - Saito, Yutaka (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Pancreatobiliary Association; Korean Society of Gastrointestinal Cancer, 2013)
Due to the widespread acceptance of gastric and esophageal endoscopic submucosal dissections (ESDs), the number of medical facilities that perform colorectal ESDs has grown and the effectiveness of colorectal ESD has been increasingly reported in recent years. The clinical indications for colorectal ESD at the National Cancer Center Hospital, Tokyo, Japan include laterally spreading tumor (LST) nongranular type lesions >20 mm and LST granular type lesions >30 mm. In addition, 0-IIc lesions >20 mm, intramucosal tumors with nonlifting signs and large sessile lesions, all of which are difficult to resect en bloc by conventional endoscopic mucosal resection (EMR), represent potential candidates for colorectal ESD. Rectal carcinoid tumors less than 1 cm in diameter can be treated simply, safely, and effectively by endoscopic submucosal resection using a ligation device and are therefore not indications for ESD. The en bloc resection rate was 90%, and the curative resection rate was 87% for 806 ESDs. The median procedure time was 60 minutes, and the mean size for resected specimens was 40 mm (range, 15 to 150 mm). Perforations occurred in 23 (2.8%) cases, and postoperative bleeding occurred in 15 (1.9%) cases, but only two perforation cases required emergency surgery (0.25%). ESD was an effective procedure for treating colorectal tumors that are difficult to resect en bloc by conventional EMR. ESD resulted in a higher en bloc resection rate as well as decreased invasiveness in comparison to surgery. Based on the excellent clinical results of colorectal ESDs in Japan, the Japanese healthcare insurance system has approved colorectal ESD for coverage.